Industrial training report: Pejabat Setiausaha Kerajaan Terengganu (PSUK) / Fatimah Nurain Mohd Khalpiah - Mohd Khalpiah, Fatimah Nurain (Pejabat Setiausaha Kerajaan Terengganu (PSUK), 2021)
Industrial training is an important part of the Bachelor's degree in Information System Management at UiTM, as it prepares students for the challenges for the industry. This industrial training goal is to improve students' knowledge and skills in a certain career in their various industries while also creating knowledgeable, creative, and competent graduates. The trainee has completed industrial training for five months between March 1st and July 31st, 2021 at the Pejabat Setiausaha Kerajaan Negeri Terengganu (PSUK) in the Bahagian Pembangunan Teknologi Maklumat (BPTM) departments, where the trainee gained a plethora of knowledge and information, particularly on system development and information technology (IT). In total, there are four chapters in this industrial training report consist of introduction, organization information, special activities, and conclusions. The importance of Chapters 3 and 4 in this industrial report was emphasized since they are critical for this entire industrial training. The primary activities that were completed during the five months of practical training at BPTM will be addressed and illustrated in detail in Chapter 3. In the meantime, Chapter 4 will be covered and analyze, which will focus on the trainee's information gained during the industrial training period, lessons learned, personal opinion, and limitations and recommendations that trainee suggest to organization.